(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2015)
In the paper the migration of copper in water–sediment system and the dependence between copper content and pH, and dissolved oxygen were investigated. The Hrazdan River was the study area, one of the largest and the most important rivers in Armenia. Samples were taken from 6 sampling points of the Hrazdan River basin (66 samples of water and bottom sediment) during 2012–2013. Results of copper content analysis reveal that none of the identified values exceed maximum permissible concentration. The correlation coefficients between copper content and, both for pH and dissolved oxygen, were obtained. The influence of pH and dissolved oxygen on migration of copper in water–bottom sediment system was identified.